EXPLORATION OF IRONY OF DESIRES THROUGH THE LENS OF PSYCHOLOGY AND MORALITY IN THEODORE DREISER’S NOVEL “SISTER CARRIE - Saakyan, Roza; Jalilova, Lola (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article delves into the intricate dynamics of human emotions, desires, and ambitions within Theodore Dreiser’s novel “Sister Carrie”. It explores the profound psychological transformations and moral dilemmas experienced by the characters. Through meticulous analysis of dialogue excerpts, it unveils the complexities of their inner worlds and the consequences of their choices. By dissecting the characters' aspirations and ethical struggles, it provides fresh perspectives on their development and the moral inquiries embedded in the narrative. Ultimately, the article offers profound insights into the interplay of personal ambition, societal expectations, and moral integrity within the novel's rich tapestry of human experience.